Elevated intraocular pressure induces neuron‐specific β‐III‐tubulin expression in non‐neuronal vascular cells. Issue 5 (29th December 2019) - Prokosch, Verena; Brockhaus, Kathrin; Anders, Fabian; Liu, Hanhan; Mercieca, Karl; Gericke, Adrian; Melkonyan, Harut; Thanos, Solon
Abstract: Purpose: Pathological alterations within optic nerve axons and progressive loss of the parental retinal ganglion cell (RGC) bodies are characteristics of glaucomatous neuropathy. Abnormally elevated intraocular pressure (IOP) is thought to be the major risk factor for most forms of glaucomatous changes, while lowering of the IOP is the mainstream of treatment. However, the pathophysiological mechanisms involved in neurodegenerative changes are poorly understood. It remains still a matter of debate whether elevated IOP harms the neurons directly or indirectly through alterations in the retinal vascularization. Methods: We analysed morphological and molecular changes within the retina exposed to elevated IOP in an animal model of glaucoma in vivo, in retinal explants and in cultured dissociated retinal cells each incubated under elevated air pressure in vitro, imitating elevated IOP. Results: Although ß‐III‐tubulin expressing RGCs decreased within the course of the disease, total amount of ß‐III‐tubulin protein within the retina increased, leading to the assumption that other cells than RGCs abnormally express ß‐III‐tubulin due to elevated IOP. Surprisingly, we found that β‐III‐tubulin, a marker developmentally regulated and specifically expressed in neurons under normal conditions, was strongly up‐regulated in desmin‐, PDGFR‐β‐ and α‐SMA‐positive pericytes as well as in endothelin‐1‐positive endothelial cells both in vivo under elevated IOP and in vitro under elevated culture atmosphere pressure that simulated IOP elevation. Beta‐III‐tubulin‐driven signalling pathways (ERK 1/2, pERK1/2 and cdc42/Rac) were also regulated. Conclusion: The unprecedented regulation of neuron‐specific β‐III‐tubulin in pericytes and endothelial cells is likely associated with a role of the retinal vasculature in the IOP‐induced development and manifestation of glaucomatous degenerative optic nerve response.